Synthesis of Silver Nanoparticles from the Aqueous Extract of Leaves of Ocimum sanctum for Enhanced Antibacterial Activity - Charusheela Ramteke; Tapan Chakrabarti; Bijaya Ketan Sarangi; Ram-Avatar Pandey (Journal of Chemistry)
The field of nanotechnology is the most active area of research in modern materials science. Though there are many chemical as well as physical methods, green synthesis of nanomaterials is the most emerging method of synthesis. We report the synthesis of antibacterial silver nanoparticles (AgNPs) using leaf broth of medicinal herb, Ocimum sanctum (Tulsi). The synthesized AgNPs have been characterized by UV-Vis spectroscopy, transmission electron microscopy (TEM), and X-ray diffractometry. The mean particle of synthesized NPs was found to be 18 nm, as confirmed by TEM. The qualitative assessment of reducing potential of leaf extract has also been carried out which indicated presence of significant amount of reducing entities. FTIR analysis revealed that the AgNPs were stabilized by eugenols, terpenes, and other aromatic compounds present in the extract. Such AgNPs stabilized by Tulsi leaf extract were found to have enhanced antimicrobial activity against well-known pathogenic strains, namely Staphylococcus aureus and E. coli.